ANALISIS METODE PELAKSANAAN PEKERJAAN PENGECORAN DENGAN READY MIX (STUDI KASUS: PEMBANGUNAN MALL PELAYANAN PUBLIK TABANAN): Analysis Of Casting Work Implementation Methods Using Ready Mix (Case Study: Construction Of The Tabanan Public Service Mall) - Hermawan, I Putu Yana; Diputera, I Gede Angga; Lestari, I Gusti Agung Ayu Istri; Putra, I Gede Widiantara (Ganec Swara, 2025)
Structural work, especially in the casting process, plays an important role. One of the methods that can be used is casting with ready mix concrete, because of the better time efficiency than conventional methods. The purpose of this study is to find out about the stages, specifications and technical requirements on the 2nd floor plate. A case study on the construction of the Tabanan Public Service Mall located in Banjar Anyar, Kediri District, Tabanan Regency. The research method used is a quantitative method, the data used is the Cost Budget Plan (RAB) analyzed to obtain the description of the work and volume, the plan drawing is used for the creation of work drawings, the time schedule is used as a reference in the duration of the work, the Unit Price Analysis of Work is used to obtain the resource coefficient and resource price. From the job description data, the stages of the activity are obtained, the plan drawings produce work drawings, and the time schedule produces the duration of the work. The results of the study obtained that in the stages of casting work with ready mix on the 2nd floor plate in scaffolding work there are 5 stages of activities, bodeman work 3 stages of activities, B1 beam formwork 30 x 50 cm and B2 beam formwork 25 x 35 cm there are 4 stages of activities, B1 beam and B2 beam ironing work there are 3 stages of activities, Formwork with bondek plates has 5 stages of activities, wiremesh ironing work has 3 stages of activities, casting work with ready mix on the 2nd floor plate has 3 stages of activities.